2016
DOI: 10.1186/s40064-016-3194-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of human enteroviruses associated with aseptic meningitis in Yunnan province, Southwest China

Abstract: Human enteroviruses (EVs) are the major causative agents of aseptic meningitis. In this study, a total of 524 children were admitted to the children Kunming hospital (continental China) for aseptic meningitis manifestations in 2009 and 2010. An EV infection was diagnosed in 85/524 children (16.2 %) and the viruses detected were assigned to 16 serotypes. Most serotypes belonged to the enterovirus B species. Echovirus 9 was predominant (24.7 %), followed by coxsackievirus B5 (23.5 %) and then echovirus 30 (16.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 38 publications
5
16
1
Order By: Relevance
“…In this study, we studied the etiology of VE and VM among children in Hebei province, China. During the study period, the most common causative pathogens of VE and VM were EVs, followed by HSV1 and VZV, which is consistent with results of previous studies conducted in China . EVs accounted for 55.7% (98/176) and 64.6% (53/82) of all cases of VE and VM with confirmed viral etiology, respectively.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, we studied the etiology of VE and VM among children in Hebei province, China. During the study period, the most common causative pathogens of VE and VM were EVs, followed by HSV1 and VZV, which is consistent with results of previous studies conducted in China . EVs accounted for 55.7% (98/176) and 64.6% (53/82) of all cases of VE and VM with confirmed viral etiology, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the major EV serotypes observed were E6 and E30, which were detected in 25.0% and 17.3% of cases in 2014, respectively. E18, which was detected at low prevalence in mainland China in previous studies, became the predominant EV serotype causing VE and VM in Hebei province in 2015 . The E18 serotype of EV‐B has caused many outbreaks of aseptic meningitis in the USA, Japan, Germany, and other regions .…”
Section: Discussionmentioning
confidence: 97%
“…The height and size of the top three genes, differently colored, was proportional to their RRA scores. especially echovirus, is the dominant serotype in the cerebrospinal fluid of patients (Chen et al, 2017;Zhu et al, 2016). It remains obscure how EV-B viruses cross the blood-brain barrier to cause these neurological diseases.…”
Section: Data Resourcesmentioning
confidence: 99%
“… 6 So far, there has been no report of an E18-associated encephalitis/meningitis outbreak in mainland China, but little E18 epidemiological data is available. 7 Here we describe an outbreak of E18 encephalitis/meningitis in children that occurred in Hebei Province, China, in 2015.…”
mentioning
confidence: 99%